Outrunning the gender gap: Boys and girls compete equally - Anna Dreber; Emma von Essen; Eva Ranehill (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
Recent studies find that women are less competitive than men. This gender difference in competitiveness has been suggested as one possible explanation for why men occupy the majority of top positions in many sectors. In this study we explore competitiveness in children, with the premise that both culture and gendered stereotypes regarding the task at hand may influence competitive behavior. A related field experiment on Israeli children shows that only boys react to competition by running faster when competing in a race. We here test if there is a gender gap in running among 7-10 year old Swedish children. We also introduce two female sports, skipping rope and dancing, to see if competitiveness is task dependent. We find no gender difference in reaction to competition in any task; boys and girls compete equally. If gender equality matters for competitiveness, this result may be explained by cultural factors, since Sweden scores higher on gender equality indices than Israel.
Keywords: C93; D03; J16; 330; competitiveness; gender differences; field experiment; Kinder; Geschlecht; Wettbewerb; Verhalten; Test; Schweden